2011
DOI: 10.1200/jco.2011.34.7872
|View full text |Cite
|
Sign up to set email alerts
|

Missense Mutations Located in Structural p53 DNA-Binding Motifs Are Associated With Extremely Poor Survival in Chronic Lymphocytic Leukemia

Abstract: The substantially worse survival and the short TTFT suggest a strong mutated p53 gain-of-function phenotype in patients with CLL with DBMs mutations. The impact of p53 DBMs mutations on prognosis and response to therapy should be analyzed in investigative clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 37 publications
7
46
0
Order By: Relevance
“…In addition, frameshift or in-frame deletions were found exclusively in EGFR-mut patients. Although most studies on the prognostic role of p53 in human cancers have only dealt with wt versus mutated patients, recent reports have demonstrated the usefulness of categorizing TP53 mutations since different mutant proteins can have widely disparate biologic effects (14,17,18). Our study strongly supports this new approach: we found that only nondisruptive mutations were significantly associated with worse OS, whereas TP53 mutations as a whole did not significantly correlate with outcome.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, frameshift or in-frame deletions were found exclusively in EGFR-mut patients. Although most studies on the prognostic role of p53 in human cancers have only dealt with wt versus mutated patients, recent reports have demonstrated the usefulness of categorizing TP53 mutations since different mutant proteins can have widely disparate biologic effects (14,17,18). Our study strongly supports this new approach: we found that only nondisruptive mutations were significantly associated with worse OS, whereas TP53 mutations as a whole did not significantly correlate with outcome.…”
Section: Discussionsupporting
confidence: 78%
“…The small numbers of patients included in some of these studies, the differences in follow-up, and the various criteria used to classify TP53 mutations have led to contradictory results. This last aspect is particularly important as the heterogeneity of TP53 mutations has been demonstrated to correlate with similarly heterogeneous clinical outcomes in other types of tumor (14,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Saleem et al analyzed loss of function mutations in p53 gene in the patients of oral squamous cell carcinoma and found that AGT to ACT missense mutation in DNA binding domain may result in impaired p53 function. In chronic lymphocytic leukemia patients, missense mutations in DNA binding motif were correlated with poor survival [154,155]. p53 has been considered as a significant player of apoptosis in many studies, and there is a growing accumulation of articles revealing its role in many malignancies.…”
Section: Death Receptormentioning
confidence: 99%
“…Recent discoveries indicate that the transcriptional activity of P53 also determines important biological processes such as metabolism via regulation of tigar (6)(7)(8) and sco2 (8)(9)(10), embryonic development of cardiomyocytes through Nkx2.5 and TroponinT2 (11), and non-cell autonomous signaling in the tumor microenvironment (12), suggesting a critical role for P53 in the regulation of basic processes of human biology. Truncation (13), transactivation domain (14), DNA-binding domain (15), and tetramerization domain mutations in the p53 gene (16) impair the ability of P53 to interact with chromatin (17,18). This eventually results in the loss of P53's transcriptional activity towards downstream effector genes involved in anticancer signaling (2,13,19).…”
Section: Introductionmentioning
confidence: 99%